Analysis of the Use of Kindergarten Watching Siaga Bencana Learning Model for Structured Positive Thinking Ability on Early Childhood - Lina Amelia; Fitriah Hayati; Sri Milfayetti; Ichsan Ichsan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The Kindergarten Watching Siaga Bencana Learning Model for early childhood has been tested for 2 years in three schools using development research methods. Urgenci of this research is to provide knowledge and skills to young children in dealing with disasters, especially the earthquake and tsunami. In this study children will be taught through a scientific approach to posture (scientific positive and structured thinking). Realizing learning in accordance with the stages of growth and development of early childhood. This research approach uses the research and development (R&D) method of the Thiagarajan model which consists of 4 stages known as the 4-D model (Four-D model). These stages are the defining stage (Define), the design stage (Design), the development stage (Develop), and the Disseminate stage. the study was conducted over 2 years with details: the first year was the defining stage (Define) and the design stage (Design). The second year was implemented the development stage (Develop), and the Deployment stage (Disseminate). By year 1 it had been reached the model's definition and design stages. The defining stage (Define) is complete, the design stage (Design) model with the following stage summary:1) has been analyze the geographical environmental conditions of the child is associated with earthquake disasters and relevant intelligence theories is completed with the obtainance of the initial trial site of TK syeikh abdurrauf area Blang Oi located about 1.9 KM from the seashore of ulhele, 2) Analysis of learner to draft learning previews, identify key parts to be taught and systematically compose topics to be taught, task analysis and learning purpose specifications, design prototype learning devices (test drafting, media selection and manufacture, format selection, drafting activity implementation procedures are complete. In the second year, the team has come to the field, namely 3 schools. This article will discuss the use of the Kindergarten Watching Siaga Bencana Learning Model in practicing positive and structured thinking skills in early childhood. The description of the results of the analysis each step applied in this model can train the ability to think positively and structured children. Starting from the provision of knowledge through school environment surveys, then mapping in the form of mini models and presenting them. This positive structured thinking can also be trained in the provision of knowledge and skills about earthquakes and tsunamis to children, namely at the micro and macro simulation stages of the earthquake and tsunami.